2019
DOI: 10.21037/tcr.2019.08.40
|View full text |Cite
|
Sign up to set email alerts
|

Transradial access chemoembolization for hepatocellular carcinoma in comparation with transfemoral access

Abstract: Background: This study aimed to compare the safety and efficacy of transradial access (TRA) with transfemoral access (TFA) chemoembolization in treatment of hepatocellular carcinoma (HCC).Methods: HCC patients who were late for curative treatment on initial diagnosis or HCC patients who had undergone one or several rounds of transarterial chemoembolization (TACE) were enrolled. The clinical and angiographic characteristics, the procedure related details, and the follow-up data from patients who underwent TRA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Technical success was achieved by distal radial access in 41 (97.6%) cases; therefore, distal radial access proved to be highly effective in patients undergoing DEB-TACE. Du et al reported a similar technical success rate (95% and 98.8%, respectively) in a cohort of 112 patients undergoing 160 TACEs via conventional radial access and in a cohort of 107 patients undergoing 163 TACEs via femoral access [37]. Park et al observed a 97.9% technical success rate in 47 non-coronary endovascular procedures performed via distal radial access, including 19 (40.4%) TACE [38].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Technical success was achieved by distal radial access in 41 (97.6%) cases; therefore, distal radial access proved to be highly effective in patients undergoing DEB-TACE. Du et al reported a similar technical success rate (95% and 98.8%, respectively) in a cohort of 112 patients undergoing 160 TACEs via conventional radial access and in a cohort of 107 patients undergoing 163 TACEs via femoral access [37]. Park et al observed a 97.9% technical success rate in 47 non-coronary endovascular procedures performed via distal radial access, including 19 (40.4%) TACE [38].…”
Section: Discussionmentioning
confidence: 80%
“…In our case series, only a case of conversion to femoral access was recorded (2.4% conversion rate). In a recent case series of 112 patients who underwent 160 TACEs by conventional radial access [37], 1.9% of cases underwent crossover to femoral access for selective cannulation failure. Al-Azizi [41] reported a conversion rate of 1.7% due to a case of severe tortuosity of the left subclavian artery resulting in unsuccessful cannulation of the right coronary artery and an additional right radial artery cannulation.…”
Section: Discussionmentioning
confidence: 99%
“…8,19 In our study, we achieved a technical success rate of 95% (39/41) in the RAA group, which is similar to the results of Du et al who reported a technical success rate of 95% (152/160) in the RAA group and 98.8% (161/163) in the FAA group, with no differences between the two approaches (P = .102). 5 Similarly, Ghosh et al reported a 100% technical success rate between RAA (90/90) and FAA (56/56). 25 In another study, Wan et al reported 92.3% (24/26) technical success rate for hepatic arterial infusion chemotherapy using RAA and 100% (43/43) technical success rate using FAA in their retrospective cohort (P = .139) and 100% technical success rate using RAA or FAA in their prospective cohort.…”
Section: Discussionmentioning
confidence: 93%
“…One study reported a greater incidence of access-site complication with RAA with a rate of radial artery occlusion (RAO) up to 33% (11 out of 33 TACEs) 21 whereas other studies reported lower rates of access site complication with RAA. 5,22 The purpose of this study was to compare the technical success rate, the selectivity of TACE, the complication rate, the radiation dose given to the patients and the hospitalization stay between TACE performed using FAA and TACE performed using RAA in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, complete hemostasis was achieved in almost 3 to 6 hours with a slight compression bandage with an air sac over the access site for the proximal RA access site. [20–22] In our study, complete hemostasis was achieved with a slight compression bandage with gauze applied over AS. And DRA in the AS indeed had significantly reduced hemostasis time: approximately 2 hours for cases without coagulation function abnormal.…”
Section: Discussionmentioning
confidence: 98%